The three parties in the race to the bottom: host governments, home governments and multinational companies - Rosanne Altshuler; Harry Grubert (Rutgers University, Department of Economics, 2005)
Most studies of tax competition and the race to the bottom focus on potential host countries competing for mobile capital, neglecting the role of corporate tax planning and of home governments that facilitate this planning. This neglect in part reflects the narrow view frequently taken of the policy instruments that countries have available in tax competition. For example, high-tax host governments can permit income to be shifted out to tax havens as a way of attracting mobile companies. Home countries will cooperate in this shift if they think the benefit to their companies is greater than any reduction in the domestic tax base. We use various types of U.S. data, including firm level tax files, to identify the role of the three parties (host governments, home governments and MNCs) in the evolution of tax burdens on U.S. companies abroad from1992 to 2002. This period is of particular interest because the United States introduced regulations in 1997 that greatly simplified the use of more aggressive tax planning techniques. The evidence indicates that from 1992 to 1998 the decline in effective tax rates on U.S. companies was driven largely by host governments defending their market share. But after 1998, tax avoidance behavior seems much more important. Effective tax rates on U.S. companies had a much weaker link with local statutory tax rates. Furthermore, the disparity in the reported profitability of subsidiaries in high-tax and low-tax jurisdictions grew substantially. After 1997, there was a very large growth in intercompany payments and a parallel growth of holding company income. We attempt to estimate how much of these payments were deductible in the host country, and conclude that by 2002 the companies were saving about 7.0 billion per year by using the more aggressive planning strategies. This amounts to about 4 percent of foreign direct investment income and about 15 percent of their foreign tax burden.
Keywords: 330